Robert Entman’s Framing Analysis: Female Representation in 2024 Presidential Candidates on Republika.com and Sindonews.com - Ayub Dwi Anggoro; Fingky Ayu Puspitasari; Ahmad Puad Mat Som (Komunikator, 2023)
Women’s participation in the presidential election is still low, and they rarely appear in surveys and news as candidates for the 2024 Presidential election. Women are often considered more suitable to lead in the domestic sphere and less suitable for the public sphere. The role of the media in shaping people’s views on women in politics is crucial. This study uses a qualitative approach and Robert M. Entman’s framing analysis to examine news from Republika.com and Sindonews.com related to the presence of female candidates as 2024 Indonesian presidential candidates. The results showed that Sindonews.com tends to highlight the existence of female candidates positively but too narrowly focuses on gender aspects and stereotypical views of women as vice presidential candidates. Meanwhile, news from Republika.com focuses more on analyzing electability factors and political party support for female candidates, presenting a positive view of women as alternative presidential candidates. The role of the media in constructing reality must positively impact increasing women’s representation in Indonesian politics. However, the media must also be able to avoid bias and present objective and consistent information.